Reinterpellation And Reimitation Of Conservative Ideology Of Salafi Through The Mediatization Of Religion On Instagram Rodja Tv. - Makroen Sanjaya; Andi Faisal Bakti; Ridzki Rinanto Sigit; Rulli Nasrullah (Eduvest - Journal of Universal Studies, 2022)
The Salafist community, which is marginalized from mainstream media in Indonesia, represents the ideology of Salafus Salih through the mediatization of religion. Salafists originally preached traditionally but later utilized radio and television and then websites and social media. This ideological representation through the mediatization of religion increases the number of followers so that they can reproduce social formations to maintain the status quo. For this reason, this study aims to reveal how Salafists represent the conservative ideology of Salafus Salih through the mediatization of religion on Rodjatv's Instagram. Using a critical paradigm and mediatization of religion theory with virtual ethnographic methods, this study explains how the conservative ideology of Salafus Shalih in the mediatization of religion through three media metaphors, media as a channel, language, and environment, is instilled by the Salafi group to its followers. The results revealed that the Salafi da'wah content in Rodja's media interpellated the new Salafis and imitated the religious way of Salafus Salih while creating a large number of communities or congregations. The new Salafi followers then interpellated (re-interpellation) and imitated (reimitation) to the next follower. The series of re-interpellations and limitations ultimately constituted the Salafi da'wah and the ideological congregation of Salafus Salih